2012
DOI: 10.1177/1470320312439493
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a single-pill fixed-dose combination of high-dose telmisartan/hydrochlorothiazide in patients with uncontrolled hypertension

Abstract: High-dose telmisartan/HCTZ therapy was associated with a significant reduction in BP and helped patients achieve their target BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…To our knowledge, however, there is no clinical report that telmisartan may decrease SUA level, whereas some clinical studies have shown a lowering effect of losartan on SUA level. In patients with hypertension, high-dose treatment with telmisartan for three months significantly increased SUA level [28]. In this study, we showed that long-term monotherapy with telmisartan increased SUA level.…”
Section: Discussionsupporting
confidence: 52%
“…To our knowledge, however, there is no clinical report that telmisartan may decrease SUA level, whereas some clinical studies have shown a lowering effect of losartan on SUA level. In patients with hypertension, high-dose treatment with telmisartan for three months significantly increased SUA level [28]. In this study, we showed that long-term monotherapy with telmisartan increased SUA level.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, we divided the patients in the AZ group into 2 groups according to the normal range. 23,24) Our "relatively high UA" was defined as UA > 6.0 mg/dL, and "relatively low UA" was defined as 6.0 mg/dL ≥ UA. In AZ patients with relatively low UA, although the UA value at 3 months (5.1 ± 1.0 mg/dL) was significantly increased compared with the value at baseline (4.6 ± 1.0 mg/dL) (P < 0.01), the value was still within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Co ważne, wykazano, że połączenie dwulekowe oparte na tych dwóch substancjach jest skuteczniejsze niż monoterapia. Zastosowanie tego skojarzenia wiąże się nie tylko z istotniejszą redukcją wartości ciśnienia, ale także z większym odsetkiem pacjentów, u któ-rych udaje się osiągnąć docelowe wartości ciśnienia tętniczego krwi, co potwierdzono także w badaniach wykorzystujących ABPM w celu oceny efektu hipotensyjnego [52][53][54]. Połącze-nie dwulekowe oparte na telmisartanie jest skuteczniejsze niż to, w których podstawową składową był walsartan czy losartan (ryc.…”
Section: Telmisartan Jako Podstawowa Składowaunclassified